Companion Encyclopedia of Anthropology: Humanity, Culture and Social Life - Ingold, Tim (Taylor and Francis, 2002)
* Provides a comprehensive survey of contemporary thinking in biological, social and cultural anthropology and establishes the interconnections between these three fields. * Useful cross-references within the text, with full biographical references and suggestions for further reading. * Carefully illustrated with line drawings and photographs. 'The Companion Encyclopedia of Anthropology is a welcome addition to the reference literature. Bringing together authoritative, incisive and scrupulously edited contributions from some three dozen authors. The book achieves an impressive breadth of coverage of specialist areas.' - Times Higher Educational Supplement 'Recommended for all anthropology collections, especially those in academic libraries.' - Library Journal 'This is a marvellous book and I am very happy to recommend it.' - Reference Reviews Tim Ingold , University of Manchester, UK; Phillip V. Tobias , University of the Witwatersrand Medical School, South Africa; Clive Gamble , University of Southampton, UK; Philip Lieberman , Brown University, USA; David Premack University of Pennsylvania, USA; Thomas Wynn , University of Colorado at Colorado Springs, USA; Roy Ellen , University of Kent, UK; Igor de Garine , France; Mark N. Cohen , State University of New York College, USA; Stephen Kunitz , University of Rochester Medical Center, USA; John Olding-Smee , Brunel University, UK; Mary L. Foster, University of California Berkley, USA; Daniel Miller , University College London, UK; Francois Sigaut , Centre de Recherches Historiques, France; Brent Berlin , University of California, USA; Amos Rapoport , University of Wisconsin at Milwaukee, USA; Barbara E. Adams , University of Wales, UK.; Brian V. Street , University of Sussex, UK; Niko Besnier , Yale University, USA; Gilbert Lewis , University of Cambridge, UK; James F. Weiner , Australian National University, Australia; Richard B. Schechner , New York University, USA; Howard Morphy , University of Oxford UK; Anthony D. Smith , London School of Economics, UK; Robin Dunbar , University College London, UK; Alan Barnard , University of Edinburgh, UK; Fitz John Porter Poole , University of California, San Diego, USA; J. de Bernadi , Henrietta L. Moore , University of Cambridge, UK; Sutti Ortiz , Boston University, USA; Chris Gregory , Australian National University, Australia; Simon Roberts , London School of Economics, UK; Robert A. Rubinstien , Northwestern University, USA; Timothy Earle , University of California, USA; Andre Beteille , University of Delhi, India; Peter Worsley . 'Ingold's Companion Encyclopedia deserves to be a lifelong companion for researchers and students who need more than potted information.' - Anthropology Today 'There is no truly comparable work. This book is an essential asset for university and anthropological libraries and a useful addition to any reference library.' - The Year in Reference Tim Ingold is at the University of Manchester.